Neoliberal securitisation and symbolic violence: silencing political, academic and societal resistance - Kamali, Masoud (Palgrave Macmillan, 2021)
Chapter 1. Introduction -- Chapter 2. Theoretical Perspectives -- Chapter 3. Securitisation and self-censorship in mainstream political parties -- Chapter 4. Securitisation and self-censorship in mainstream mass media -- Chapter 5. Securitisation and self-censorship in academia -- Chapter 6: Securitisation and self-censorship in civil society -- Chapter 7: Conclusions.